Improved coining force calculations through incorporation of key process parameters. Issue 1 (November 2020) - Cotton, D; Maillard, A; Kaufmann, J
Abstract: Among the sheet forming processes, coining is a specific operation which makes it possible to correct shape defects or to perform thickness reductions in the parts. This operation often requires a very high force which is likely to have an impact on the functioning of the tool or the press. It is therefore important that the coining forces be evaluated accurately, but this is not allowed by the existing analytical calculation formulas. The objective of this study is to improve the accuracy of the calculation of the coining forces via the adaptation of an existing formula. Such adaptation was carried out based on a study of the influence of the flat coining parameters. To that end, a series of experimental measurements was performed. An instrumented force measuring setup made it possible to measure the maximum coining force. Several parameters were analysed, including the coining ratio and the sheet thickness. Numerical simulations were carried out at the same time, in order to understand the influence of certain parameters on the coining force. 2D numerical models were developed using the Forge NXT2 software. The simulations and the experimental tests were analysed and the results revealed the influential phenomena which have to be taken into account in the analytical formula, in particular the coining surface and the friction. In order to study the friction more thoroughly, ring compression tests were performed so as to determine the friction coefficients, based on the Coulomb's law limited to Tresca. This type of test is representative of the stresses undergone by the metal during the coining operation. Finally, a new calculation formula is proposed, in order to integrate the coining surface and friction more accurately.